The recast European Insolvency Regulation: A Missed Opportunity for Restructuring Business in Europe - Maria-Thomais Epeoglou (UCL Journal of Law and Jurisprudence, 2017)
The European Insolvency Regulation, having acquired the necessary political consensus, entered into force on 31 May 2002. Ever since it has transformed cross-border insolvency within the European Union (‘EU’) from an unpredictable state of affairs to a recognisable framework for proceedings opened in one of the Member States. On 20 May 2015, a recast version of the EIR was adopted by the European Parliament and the Council of European Union, namely Regulation (EU) 2015/848 (‘RR’), constituting the culmination of complex review and sensitive compromise. On the occasion of its new era, the purpose of this article is to critically revisit the EIR. While insolvency law has traditionally been one of the most ‘depressive’ areas of law, this time the adoption of a binding, insolvency-related piece of legislation was accompanied by a declaration towards “a new approach to business failure”, promulgating thus a shift in EU’s policy. This paper endeavours to examine whether this objective will be efficiently served by the latest amendments introduced by the RR. It will point out that the Commission,despite having both the opportunity and the legislative tools to optimize the effectiveness and efficiency of the insolvency regime across the EU, did not seize it. The RR remains a conflict of law and jurisdiction Regulation, whereas substantive harmonisation has been attempted by way of soft tools, despite findings and reality requiring otherwise. For full text, please click here
Keywords: schemes of arrangement; substantial harmonisation; group of companies; secondary proceedings; COMI; Business rescue; Corporate restructuring; European Regulation; Incolvency